The Nlrp3 Inflammasome Does Not Regulate Alloimmunization to Transfused Red Blood Cells in Mice - Gibb, David R. (EBioMedicine, 2016)
Red blood cell (RBC) transfusions are essential for patients with hematological disorders and bone marrow failure syndromes. Despite ABO matching, RBC transfusions can lead to production of alloantibodies against “minor” blood group antigens. Non-ABO alloimmunization is a leading cause of transfusion-associated mortality in the U.S. Despite its clinical importance, little is known about the immunological factors that promote alloimmunization. Prior studies indicate that inflammatory conditions place patients at higher risk for alloimmunization. Additionally, co-exposure to pro-inflammatory pathogen associated molecular patterns (PAMPs) promotes alloimmunization in animal models, suggesting that RBC alloimmunization depends on innate immune cell activation. However, the specific innate immune stimuli and sensors that induce a T cell-dependent alloantibody response to transfused RBCs have not been identified. The NLRP3 inflammasome senses chemically diverse PAMPs and damage associated molecular patterns (DAMPs), including extracellular ATP and iron-containing heme. We hypothesized that activation of the NLRP3 inflammasome by endogenous DAMPs from RBCs promotes the alloimmune response to a sterile RBC transfusion. Using genetically modified mice lacking either NLRP3 or multiple downstream inflammasome response elements, we ruled out a role for the NLRP3 inflammasome or any Caspase-1 or -11 dependent inflammasome in regulating RBC alloantibody production to a model antigen.